SGLT-2 inhibitors in patients with heart failure and reduced ejection fraction with or without diabetes - Mejia-Zambrano, Henry (2022)
Objective: To determine the benefits of SGLT-2 inhibitors in patients with heart failure and reduced ejection fraction with or without diabetes. Methods: This systematic review included experimental studies, studies of SGLT-2 inhibitors in patients with heart failure with reduced ejection fraction with or without diabetes. A formal narrative synthesis of the data collected in English and Spanish. The summaries focused on qualitative analysis. The quality of evidence for each outcome was determined according to the Grading of Recommendations Assessmet, Developmet and Evaluation (GRADE) methodology. Results: In general, the primary events in patients with heart failure with reduced ejection fraction of the SGLT-2 inhibitor group were lower compared to the placebo group (IR:0.65; 95% CI 0.64-0.80; p=0.40). Results from cardiovascular death in the SGLT-2 inhibitor group were lower than in the placebo group (IR: 0.60; 95% CI 0.40-0.70; p=0.50). Adverse outcomes in patients in the SGLT-2 inhibitor group were lower than the placebo group (37% vs 42%, respectively) from the various studies. Conclusion: SGLT-2 inhibitors improve cardiovascular disorders, including heart failure with reduced and preserved ejection fraction, and also reduce cardiovascular morality in patients with or without diabetes.